Comparative chloroplast genome and transcriptome analysis on the ancient genus Isoetes from China - Yang, Yujiao; Yu, Xiaolei; Wei, Pei; Liu, Chenlai; Chen, Zhuyifu; Li, Xiaoyan; Liu, Xing (Frontiers in Plant Science, 2022)
Isoetes is a famous living fossil that plays a significant role in the evolutionary studies of the plant kingdom. To explore the adaptive evolution of the ancient genus Isoetes from China, we focused on Isoetes yunguiensis (Q.F. Wang and W.C. Taylor), I. shangrilaensis (X. Li, Y.Q. Huang, X.K. Dai & X. Liu), I. taiwanensis (DeVol), I. sinensis (T.C. Palmer), I. hypsophila_GHC (Handel-Mazzetti), and I. hypsophila_HZS in this study. We sequenced, assembled, and annotated six individuals’ chloroplast genomes and transcriptomes, and performed a series of analyses to investigate their chloroplast genome structures, RNA editing events, and adaptive evolution. The six chloroplast genomes of Isoetes exhibited a typical quadripartite structure with conserved genome sequence and structure. Comparative analyses of Isoetes species demonstrated that the gene organization, genome size, and GC contents of the chloroplast genome are highly conserved across the genus. Besides, our positive selection analyses suggested that one positively selected gene was statistically supported in Isoetes chloroplast genomes using the likelihood ratio test (LRT) based on branch-site models. Moreover, we detected positive selection signals using transcriptome data, suggesting that nuclear-encoded genes involved in the adaption of Isoetes species to the extreme environment of the Qinghai-Tibetan Plateau (QTP). In addition, we identified 291–579 RNA editing sites in the chloroplast genomes of six Isoetes based on transcriptome data, well above the average of angiosperms. RNA editing in protein-coding transcripts results from amino acid changes to increase their hydrophobicity and conservation in Isoetes, which may help proteins form functional three-dimensional structure. Overall, the results of this study provide comprehensive transcriptome and chloroplast genome resources and contribute to a better understanding of adaptive evolutionary and molecular biology in Isoetes.